Cognitive Impairment in Heart Failure: Landscape, Challenges, and Future Directions - Yang, Mengxi; Sun, Di; Wang, Yu; Yan, Mengwen; Zheng, Jingang; Ren, Jingyi (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) is a major global health-care problem accounting for substantial deterioration of prognosis. As a complex clinical syndrome, HF often coexists with multi-comorbidities of which cognitive impairment (CI) is particularly importance. CI is increasing in prevalence among patients with HF, present in around 40%, even up to 60% in elderly HF patients. As a potent and independent prognostic factor, CI significantly increases the hospitalization and mortality and decreases quality of life in patients with HF. There has been a growing awareness of the complex bidirectional interaction between HF and CI, sharing a number of common pathophysiological pathways including reduced cerebral blood flow, inflammation, and neurohumoral activations. Researches focus on the precise mechanism for CI in HF is still insufficiency. As the tremendous adverse consequences of CI in HF, effective early diagnosis of CI in HF and interventions for these patients may halt disease progression and improve prognosis. The current clinical guidelines in HF have begun to emphasize the importance of CI. However, nearly half of CI in HF is under-diagnosed and few recommendations are available to guide clinicians about how to approach CI in patients with HF. This review aims to synthesise knowledge about the link between HF and cognitive dysfunction, issues pertaining to screening, diagnosis and management of CI in patients with HF, and emerging therapies for prevention. Based on data from current studies, critical gaps in knowledge of CI in HF are identified, and future research directions to guide the field forward are proposed.